Revisiting the origins of participatory design. A review from the south (ARQUISUR Revista, 2024)
Participatory design addresses the project activity from a multiactoral and inclusive approach. Focusing on design, this article specifically reconstructs the history of a participatory approach to architectural design. It aims to recognize those concepts, practices, and tools that, since the end of the 19th century, have contributed to a participatory approach to architectural design. In opposition to those reviews limited to the central countries, this work broadens the view to integrate experiences located in the south of Latin America that contribute to understanding the topic. The results, by making experiences visible and highlighting the multiplicity of bonds with their continuity, convergence, and influence, demonstrate the complexity and depth of participatory design. Secondly, this review helps to understand the transformations of the topic in relation to its broader social and cultural context. However, some ambiguity and overlapping in the results require further research to reformulate the initial systematization.
Keywords: architecture; architectural design; history of architecture; citizen participation; urbanism